A new approach to solve a diffusion-convection problem - İnç, Mustafa; Cherruault, Y (Emerald, 2002)
We use the Adomian decomposition method to study a non-linear diffusion-convection problem (AMP). The decomposition method has been applied recently to a wide class of non-linear stochastic and deterministic operator equations involving algebraic, differential, integro-differential and partial differential equations and systems. The method provides a solution without linearization, perturbation, or unjustified assumptions. An analytic solution of NDCP in the form of a series with easily computable components using the decomposition method will be determined. The non-homogeneous equation is effectively solved by employing the phenomena of the self-cancelling 'noise terms' whose sum vanishes in the limit. Comparing the methodology with some known techniques shows that the present approach is highly accurate.
Keywords: Partial-Differential Equations; Adomian Decomposition Method; Integral-Equations; Reliable Technique; Wave-Equation; Convergence; Equality; Series